1993
DOI: 10.1007/bf00307739
|View full text |Cite
|
Sign up to set email alerts
|

Class I associations and frequencies of class II HLA-DRB alleles by RFLP analysis in children with rheumatoid-factor-negative juvenile chronic arthritis

Abstract: A total of 94 patients with juvenile chronic arthritis (JCA) was tested for HLA class I by serology and for class II by RFLP typing. Early onset JCA (EOPA) is associated with HLA-A2, DR5 and DR8 in both males and females. The combination (joint occurrence) of these JCA associated alleles (A2, DR5, DR8) is frequently seen in patients with chronic iridocyclitis. Late onset pauciarticular disease has an increased frequency of HLA-B27, especially in males. Our data confirm that polyarticular JCA with early childho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
8

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 14 publications
0
18
0
8
Order By: Relevance
“…In particular, HLA-A2 allele is associated with different JIA subtypes, especially those with earlier onset [15][16][17]. Enthesitis-related JIA is associated with HLA-B27, whereas oligoarticular JIA has been shown to be associated with HLA-A2, DR5, and DR8 [15][16][17]. The infrequent observation of HLA DRB1*04 and DRB1*07 in children with oligoarthritides should suggest the protective role exhibited by these haplotypes.…”
Section: Genetic Predisposing Factors To Juvenile Idiopathic Arthritismentioning
confidence: 91%
See 2 more Smart Citations
“…In particular, HLA-A2 allele is associated with different JIA subtypes, especially those with earlier onset [15][16][17]. Enthesitis-related JIA is associated with HLA-B27, whereas oligoarticular JIA has been shown to be associated with HLA-A2, DR5, and DR8 [15][16][17]. The infrequent observation of HLA DRB1*04 and DRB1*07 in children with oligoarthritides should suggest the protective role exhibited by these haplotypes.…”
Section: Genetic Predisposing Factors To Juvenile Idiopathic Arthritismentioning
confidence: 91%
“…The infrequent observation of HLA DRB1*04 and DRB1*07 in children with oligoarthritides should suggest the protective role exhibited by these haplotypes. Rheumatoid factor-negative polyarticular JIA is mainly associated with DRB1*08 and DPB1*03, whereas the rheumatoid factorpositive polyarticular variant is associated with DRB1*04, DQA1*03, and DQB1*03 haplotypes [15][16][17]. In the end, HLA DRB1*01 and DQA1*010 have been associated with the psoriatic variant of JIA [15][16][17].…”
Section: Genetic Predisposing Factors To Juvenile Idiopathic Arthritismentioning
confidence: 95%
See 1 more Smart Citation
“…Several studies have reported association of JRA with different human HLA class II alleles by either serological or DNA typing techniques, but the majority of these findings come from studies performed in whites [13][14][15][16]. For the polyarticular JRA, the alleles HLA-DB1*0401, DRB1*01, and DRB1*08 have been found to be associated with susceptibility [17][18][19][20][21][22][23][24][25][26]. For the pauciarticular or oligoarticular onset, which is the most common and most extensively studied subgroup, the alleles HLA-DRB1*08, DRB1*11, DRB1*13, and DQB1*0402 [18 -19] are associated with susceptibility.…”
Section: Introductionmentioning
confidence: 99%
“…Above-normal frequencies have been found in JCA patients with both the polyarticular and the pauciarticular-onset subtypes [1,3,[5][6][7][8]10], although in some series this phenomenon seemed to be restricted to late-onset pauciarticular disease [4,12]. Only a few studies have shown elevated frequencies in seropositive adult-type JCA [11] or in Still's disease [8,10], whereas several others have revealed normal [3,4,10,[12][13][14] or only marginally elevated frequencies in these subtypes of JCA or in JCA patients in general [2,[15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%